2019
DOI: 10.1111/ffe.13142
|View full text |Cite
|
Sign up to set email alerts
|

On higher order parameters in cracked composite plates under far‐field pure shear

Abstract: This paper presents the analytical solution of the crack tip fields as well as the crack parameters in an infinitely large composite plate with a central crack subjected to pure shear loading. To this end, the complex variable method is employed to formulate an asymptotic solution for the crack tip fields in an anisotropic plane. Using a stress-based definition of the crack tip modes of loading, only the mode II crack parameters are found to be non-zero under pure shear load. Special focus is given to the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
(127 reference statements)
0
8
0
Order By: Relevance
“…To illustrate the impact of higher order coefficients on the crack tip stress field, we herein refer to a representative numerical example from the literature (Shah et al, 2006b;Tran and Mear, 2018;Ayatollahi et al, 2020). The problem geometry is shown in mesh grid in Fig.…”
Section: Discussion On Higher Order Termsmentioning
confidence: 99%
See 2 more Smart Citations
“…To illustrate the impact of higher order coefficients on the crack tip stress field, we herein refer to a representative numerical example from the literature (Shah et al, 2006b;Tran and Mear, 2018;Ayatollahi et al, 2020). The problem geometry is shown in mesh grid in Fig.…”
Section: Discussion On Higher Order Termsmentioning
confidence: 99%
“…Thereafter, Lee (2016Lee ( , 2018 continued their previous study (Lee et al 1996) and analysed the propagating crack in an anisotropic medium, with stress and displacement fields given along with a generic solution for all the crack parameters in dynamic fracture. More recently, Ghouli et al (2020); Nejati et al (2021b) suggested infinite series solutions for stress, strain and displacement fields in cracked anisotropic planes, while decomposing fracture modes according to a stress-based definition. These authors also devised exact analytical solutions for all crack tip coefficients in centrally cracked infinite anisotropic plates.…”
Section: Crack Tip Fields In Anisotropic Planes: Infinite Series Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic equation normally returns distinct complex roots (µ µ 1 2 ) in general anisotropic problems. Ghouli et al [35] put forward a stress-based definition for the anisotropic fracture modes based on the criterion that at =°= 0 , 0…”
Section: Nomenclature Amentioning
confidence: 99%
“…Evaluated from Eqs. (7) and (8), the coefficients of the second terms, A 2 and B 2 , construct two physical parameters, T and [35]:…”
Section: Nomenclature Amentioning
confidence: 99%